2018
DOI: 10.1080/19476337.2018.1475423
|View full text |Cite
|
Sign up to set email alerts
|

A review on the use of hormones in fish farming: Analytical methods to determine their residues

Abstract: Hormones are used in fish farming to increase fish production when one sex of a species has the capacity to grow bigger and faster than the other sex. The technique to increase fish production based on sexual dimorphism mostly uses estrogens and androgens. These chemicals must be handled carefully to ensure environmental, biological and food safety, since they can contaminate the environment and promote changes in the endocrine system inducing adverse effects on the consumer health. Another important issue is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 88 publications
1
49
1
6
Order By: Relevance
“…This indicated that golden rabbitfish were impacted by exogenous hormones in captivity. However the latency period were observed longer in compared to others (Hoga et al, ).…”
Section: Discussioncontrasting
confidence: 51%
“…This indicated that golden rabbitfish were impacted by exogenous hormones in captivity. However the latency period were observed longer in compared to others (Hoga et al, ).…”
Section: Discussioncontrasting
confidence: 51%
“…Hasil penelitian menunjukkan bahwa pemberian hormon Oodev pada pakan dapat meningkatkan pertumbuhan dari ikan giru yang diberi perlakuan. Diketahui bahwa Oodev merupakan produk hormon yang mengandung hormon GnRH dan antidopanim yang sering digunakan untuk pematangan gonad tahap awal pada ikan (Hoga et al 2018). GnRH merupakan neurohormon yang berperan dalam proses stimulus dan sintesis gonadotropin.…”
Section: Hasil Dan Pembahasanunclassified
“…GnRH merupakan neurohormon yang berperan dalam proses stimulus dan sintesis gonadotropin. Pada vertebrata termasuk ikan, peningkatan serum gonadotropin dalam darah memberikan feedback positif terhadap sekresi Leptin dan Neuropeptida Y (NPY) yang diketahui berpengaruh dalam regulasi pertumbuhan somatik (Cortes 2012;Hoga et al 2018). Dalam penelitian ini tidak dilakukan pengukuran serum Leptin maupun NPY namun mekanisme kedua hormon ini dapat menjelaskan pertumbuhan yang terjadi pada ikan giru yang diberi perlakuan hormon Oodev.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…This technique used for increase in fish production based on sexual dimorphism uses hormones-androgens and estrogens. Androgens and estrogens must be handled with care therefore, and fish adequately managed to ensure success (Hoga et al,2018).…”
Section: Introductionmentioning
confidence: 99%